ANALYSIS OF THE MAIN CHARACTER’S EMOTIONAL JOURNEY IN TERE LIYE’S NOVEL SENDIRI: A REVIEW OF LITERARY PSYCHOLOGY FROM THE PERSPECTIVE OF ELISABETH KUBLER ROSS - Purwanto, Joko; Fitriyanti, Riska; Kamaliyah, Anik Maromatul; Ferina, Rita; Permataningtyas, Dea (Journal International Inspire Education Technology, 2024)
Losing a loved one is an emotionally disruptive experience that often reshapes an individual’s inner world. Tere Liye’s novel Sendiri portrays this turmoil through the protagonist’s struggle after the death of a partner. This study aims to examine how the main character navigates her emotional transformation throughout the grieving process. Using a qualitative descriptive approach, the analysis draws on narrative excerpts from the novel and interprets them through Elisabeth Kübler-Ross’s five stages of grief. Data were collected using reading and note-taking techniques and analyzed through content analysis. The findings show that the protagonist’s grief is not merely a linear progression through denial, anger, bargaining, depression, and acceptance, but a complex journey marked by hesitation, emotional relapse, and gradual self-reconstruction. Her movement toward acceptance reflects not only the recognition of loss but also the emergence of renewed meaning and personal resilience. This highlights that grief in the novel functions as a transformative psychological journey rather than simply a sequence of emotional responses.